Elided Clausal Conjunction Is Not the Only Source of Closest‐Conjunct Agreement: A Picture‐Matching Study. (5th April 2019) - Arsenijević, Boban; Willer‐Gold, Jana; Aljović, Nadira; Čordalija, Nermina; Kresić Vukosav, Marijana; Leko, Nedžad; Malenica, Frane; Marušič, Franc Lanko; Milićev, Tanja; Milićević, Nataša; Mišmaš, Petra; Mitić, Ivana; et al.
Abstract: A recurring hypothesis about the agreement phenomena generalized as closest‐conjunct agreement takes this pattern to result from reduced clausal conjunction, simply displaying the agreement of the verb with the nonconjoined subject of the clause whose content survives ellipsis (Aoun, Benmamoun & Sportiche 1994, 1999; see also Wilder 1997). Closest‐conjunct agreement is the dominant agreement pattern in the South Slavic languages Slovenian and Bosnian/Croatian/Serbian. A natural question is whether closest‐conjunct agreement in these varieties may indeed be analyzed as entirely derived from conjunction reduction. In this article, we report on two experiments conducted to test this. The results reject the hypothesis as far as these languages are concerned, thereby upholding the relevance of models developed to account for closest‐conjunct agreement within theories of agreement.